Wood energy in sub-Saharan Africa: how to make a shadow business sustainable - Harry Hoffmann; Michael Brüntrup; Clara Dewes (Deutsches Institut für Entwicklungspolitik (DIE), 2016)
There is no getting away from it: wood is, and will remain crucial for meeting global energy demands, in particular those of the poor. Although wood provides `only' about 10% of total global primary energy, it is the most important source of energy in many parts of the developing world. Around 2.8 billion people worldwide consume wood-based fuels on a daily basis. In sub-Saharan Africa (SSA), 70% of households depend on wood energy. In several SSA countries, it makes up to 90% of household energy mix, and represents up to 3.5% of gross domestic product (GDP). As for the current trends in population growth in SSA, the amount of wood energy consumed is likely to increase in future. Even with very optimistic assumptions about renewable energy development, in 2030 wood-based energy will still be two-thirds of what it is today. Charcoal will remain the main energy source of the urban population. As they are the central component of SSA's household energy mix, production and trade of wood energy have far-reaching social, economic and environmental repercussions. Many of the poor earn a living in firewood and charcoal value chains. Charcoal has been called an “engine of pro-poor economic growth” (Van der Plas & Abdel-Hamid, 2005, p. 297). However, typically uncontrolled wood extraction has made wood energy an important force of forest and biodiversity degradation. Moreover health is threatened by traditional use, particularly of firewood. Many of the attempts in the past to control the wood energy sector have been short-sighted, top-down, and have failed. Most energy policies in SSA largely ignore the potential of wood energy as a source of reliable, storable, renewable and sustainable energy, and as the main and unavoidable energy supplier of the future. This must change! This policy brief first outlines the typical wood energy value chains in SSA, while scrutinizing unsustainable practices in every segment of the value chain. It then sketches previous, often unsuccessful interventions to manage the sector and replace wood energy. It highlights the key role of location in shaping efforts to manage the sector. Subsequently, it provides condensed policy recommendations. The primary findings of this analysis are the following: There is a strong case for pro-actively supporting the emergence of a sustainable wood energy sector. Wood energy must be recognized as an inter-sectoral issue, connected to forestry, energy, agriculture and land. Although new technologies to reduce wood and energy waste are important, governance issues remain key to attempts to manage wood fuel value chains. Previous attempts to upgrade the wood fuel value chains have been too narrow and have relied too strongly on technology and/or central state regulation and have not been able to control the sector under SSA conditions. In particular, relying on top-down prohibition, certification and central state control has disregarded the role of weak implementation capacities, local realities (informal community rules, power imbalances) and corruption in circumventing such measures. For future approaches to be successful, they need to target the multi-level nature of the wood energy sector and provide more comprehensive and location-specific interventions.
Keywords: 330; Umwelt; Ökosysteme und Ressourcen; Energie